EFEKTIVITAS SOSIAL MEDIA MARKETING DAN KUALITAS PRODUK DALAM MEMBANGUN KEPUASAN KONSUMEN - Mangihut Tampubolon; Chairman Lawvandy (LPPM UNIVERSITAS BINA INSAN, 2023)
A healthy culinary-based online store called the wrappers is a store located in Medan, North Sumatra. In the midst of increasingly fierce competition in the healthy food business, digital promotion and product quality are important factors in attracting and retaining customers. This study aims to analyze the influence of the attractiveness of digital promotions and product quality on customer satisfaction of the wrappers. The research approach used is quantitative with a survey method. The research instrument was disseminated to customers to find out their perception of digital promotion strategies and the quality of the products offered. The results of the study show that attractive, informative, and consistent digital promotions are able to strengthen the positive image of the company and increase customer interaction. Meanwhile, good product quality, such as taste, packaging, and freshness, is the main factor in shaping overall customer satisfaction. These two factors contribute significantly to the creation of sustainable satisfaction. These findings confirm that the success of a culinary business depends not only on the products offered, but also on marketing communication strategies that are executed digitally. Therefore, business actors are advised to continue to innovate in digital promotion and maintain product quality so that they can compete sustainably.